Recipes for Change validation report: Senegalese Poulet Yassa - Norman, James (2015)
The main climate risks to onion cultivation in Senegal are: (i) the availability of water resources in the major growing regions (particularly the Niayes region); (ii) increased incidence of extreme rainfall events and resulting damages to infrastructure; and (iii) the negative effects of sea level rise including inundation, erosion and salt water intrusion (again, specifically in the Niayes region). The key adaptation measures for managing the foreseen impacts of climate change upon horticulture within the region include: (i) coastal and estuary infrastructure projects to protect against hazards exacerbated by sea level rise, e.g. dikes, sea walls etc.; (ii) improved management of water resources and irrigation technologies; and (iii) interventions to support horticultural market development and smallholder market linkages. CCAFS validates the climate threats and solutions highlighted in the IFAD statements below. IFAD-identified climate threats to onions:  Rising sea levels.  Increased levels of salt in agricultural land.  Erratic rainfall and weather patterns. ASAP solutions:  IFAD helps communities adapt to climate change with techniques such as soil washing and dike building.  It also helps farmers gain easier access to markets and obtain a fairer distribution of profit.